Tajemnicza epidemia w „Georgikach” Publiusza Wergiliusza Marona. Kilka słów komentarza - Bartnik, Agnieszka (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
This article analyses an excerpt from the third song of Georgics. Virgil described a disease that attacked many animal species, including cattle, horses, sheep, pigs and humans. On the basis of the described symptoms and the number of species attacked by the plague, it should be concluded that the poet described anthrax – a zoonotic disease caused by the Bacillus anthracis bacterium.